2020
DOI: 10.1186/s13717-020-00248-3
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal analysis of urban growth on forest and agricultural land using geospatial techniques and Shannon entropy method in the satellite town of Ethiopia, the western fringe of Addis Ababa city

Abstract: Rapid conversion of conserved land and cropland to non-agricultural purposes is threatening the ecological areas and dominant agricultural activities that are the main sources of livelihood in urban fringe areas of Addis Ababa City. The combinations of government policy, socioeconomic, demographic dynamics, and biophysical triggers have driven such transformation. However, the recent fast urban expansion and infrastructural development could have accelerated the severity and rate at which urban growth impacts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(13 citation statements)
references
References 39 publications
0
12
0
1
Order By: Relevance
“…In the African highlands of this agricultural watershed, however, high and intense soil erosion is one of the most distinctive characteristics. Studies highlight that high soil erosion from agricultural watersheds causes crop production losses [ [22] , [23] , [24] , [25] , [26] ]; (Thakuriah, 2023), sedimentation of reservoirs, resulting in severe economic losses to irrigation and hydroelectric projects [ [27] , [28] , [29] ]. As a result, a study confirmed that Africa lost 40% of agricultural productivity and covered an average of one-fifth of dam storage volumes with silt [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the African highlands of this agricultural watershed, however, high and intense soil erosion is one of the most distinctive characteristics. Studies highlight that high soil erosion from agricultural watersheds causes crop production losses [ [22] , [23] , [24] , [25] , [26] ]; (Thakuriah, 2023), sedimentation of reservoirs, resulting in severe economic losses to irrigation and hydroelectric projects [ [27] , [28] , [29] ]. As a result, a study confirmed that Africa lost 40% of agricultural productivity and covered an average of one-fifth of dam storage volumes with silt [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Geographic Information System (GIS) has accelerated spatial aspects of ecotourism conservation through the identification and prioritization of potential ecotourism sites using the certain criteria for sustainable development at minimum cost and time (Ross and Wall 1999 ; Ullah and Hafiz, 2014 ; Deribew 2020 ). GIS integrates with multi-criteria decision making analysis (MCDMA) using analytic hierarchy process (AHP) based on the pair-wise comparison in ratio scale was found to be a phenomenal method to compare themes supported relative importance for the identifications of potential ecotourism zone (Saaty and Vargas 2001 ; Kumari et al 2010 ; Nino et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Rapid urban expansion has led to an increase of the urban area, encroaching into the surrounding rural areas a decrease of agricultural land and forest and the displacement of rural farming communities. The eviction of Oromo farmers from the capital's suburbs and surrounding towns has largely happened uncontrolled and favoured dispossession without compensation (Abate, 2019;Deribew, 2020;Zewdie et al, 2018).…”
Section: The Right To the City: Addis Ababa And The Oromo Questionmentioning
confidence: 99%